Preliminary Survey Tool Measuring Childhood Lead Poisoning through Spice and Home Remedy Exposure in North Carolina - Bean, Deidre (My University, 2017)
Spices and home remedies are a surprising avenue for lead poisoning in children but are all too often overlooked or under-reported due to a lack of awareness. Spices and home remedies are given to children in order to enhance flavors or relieve ailments. Lead poisoning is a common, preventable - yet detrimental - pediatric environmental public health concern. It is known to cause learning disabilities, antisocial behavior, seizures, and even death. Most alarmingly, there can be no clinical symptoms. As the United States is a melting pot of cultures, there are pockets of at risk children, especially from South Asian, Hispanic, refugees, and children in federally funded programs, such as Medicaid. It is common in these households to consume an increased amount of spices and home remedies founded in traditions, norms, and beliefs. The Childhood Lead Poisoning Prevention Program in North Carolina’s Department of Health and Human Services began to examine alternative approach in increasing level of lead exposure in respect to spices and home remedies. Registered Environmental Health Specialists make home visits to children with elevated blood lead levels and require a consistent tool with high validity to document samples taken during calls (above the threshold of 5 μg per dL). By providing a useful data collection tool, the Food and Drug Administration (FDA) will be able to present accurate data models, generating stricter regulations and testing of imported spices and home remedies. This is imperative, as it will aide in demonstrating and bringing about awareness surrounding the lead health crisis in our youth.
Keywords: Lead; Childhood Lead Poisoning; Spice; Home Remedy; Survey